2020
DOI: 10.1186/s13020-020-00345-7
|View full text |Cite
|
Sign up to set email alerts
|

The protective effects of liguzinediol on congestive heart failure induced by myocardial infarction and its relative mechanism

Abstract: Background: Heart failure (HF) is one of the most common causes of cardiovascular diseases in the world. Currently, the drugs used to treat HF in the clinic may cause serious side effects. Liguzinediol, 2, 5-dimethyl-3, 6-dimethylpyrazine, is a compound synthesized after the structural modification of ligustrazine (one active ingredient of Szechwan Lovage Rhizome). We aimed to observe the effects of liguzinediol on preventing HF and explore the related mechanisms. Methods: The ligation of left anterior descend… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…Our previous study revealed that liguzinediol has a high therapeutic effect on HF, and it could improve myocardial cell apoptosis in stress-induced HF. [24][25][26] However, it is still unknown whether liguzinediol can improve HF caused by promoting autophagy in salvaged cardiomyocytes. In this study, we aimed to establish a model of HF caused by doxorubicin (DOX) and to investigate the protective effect of liguzinediol.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study revealed that liguzinediol has a high therapeutic effect on HF, and it could improve myocardial cell apoptosis in stress-induced HF. [24][25][26] However, it is still unknown whether liguzinediol can improve HF caused by promoting autophagy in salvaged cardiomyocytes. In this study, we aimed to establish a model of HF caused by doxorubicin (DOX) and to investigate the protective effect of liguzinediol.…”
Section: Introductionmentioning
confidence: 99%
“…These alterations in cardiac morphology and function were expected as a consequence of MI and were also described in previous studies. 30,48–50 However, none of the echocardiographic parameters were improved after SFN administration. Similar results were found in a study from our group that evaluated SFN effects after infarction, 28 days after the surgery.…”
Section: Discussionmentioning
confidence: 97%
“…In addition to cardiac protection, paeoniflorin (Shao Yao Dai) inhibits tert-butyl hydroperoxide-induced mitochondrial reactive oxygen species (ROS) production in human umbilical vein endothelial cells (HUVECs) and ROS-mediated proliferation of vascular smooth muscle cells, indicating a potential therapeutic effect on diseases related to abnormal vascular remodeling [34,35]. Ligustrazine (Chuan Xiong Qin) improved cardiac function accompanied by decreased cell necrosis, collagen deposition, myocardial fibrosis, expression of pro-inflammatory factors, and oxidative stress in the Sprague-Dawley (SD) rats with myocardial infarction [36]. Ligustrazine (Chuan Xiong Qin) and paeoniflorin (Shao Yao Dai) are both the main components of ligusticum chuanxiong Hort, and they have a similar protective effect on cardiac injury.…”
Section: Ligustrazine (Chuan Xiong Qin) With Paeoniflorin (Shao Yao D...mentioning
confidence: 99%